Evaluation of radiographic measurements of the wrist in the Turkish population - Yalçın, Atilla; Polat, Abdulkadir (Journal of Surgery and Medicine, 2022)
Background/Aim: Wrist parameters measured on direct radiography are essential in diagnosing distal radius fractures and many specific wrist disorders and determining prognosis after treatment. Previous studies have shown the intercommunity variability of these parameters in the literature. To our knowledge, no study in the literature reflects the normal values in the Turkish population. This study aimed to determine the distribution and normal limits of parameters measured in posteroanterior (PA) and direct lateral radiographs of the wrist in our population between age and gender groups. Methods: In this retrospective cohort study, patients who presented to 2 centers in our clinic between 2014-2020 and had PA and lateral wrist radiographs were retrospectively reviewed. Images from patients who had no significant osseous pathology and had not undergone wrist surgery were randomly selected, and 320 (201 female, 119 male) digital images were retrospectively analyzed. The mean age was 40.45 (13.71). The sample was divided into three groups (18-30, 31-50, over 51) according to age and into two groups according to gender. Radial inclination (RI), lunate fossa inclination (LFA), cord of radiocarpal arch (cord RC), radial shift (Radsh), radial height (RadH), ulnar variance (UV), third metacarpal height (3rd MH), carpal height (CH), capitate height (CapH), lunate transverse length (LL), lunate uncovering length (LUL), scapholunate joint distance (SLD), distal radioulnar joint distance (RUD), volar tilt on lateral radiographs (VT), scapholunate angle (SLA) were measured. The lunate uncovering ratio (LUR) was measured in proportion to the lunate uncovering length (LUL) / lunate transverse length (LL); carpal height ratio (CHR) by proportioning carpal height (CH) / third metacarpal height (3rd MH); revised carpal height ratio (rCHR) was calculated by proportioning the carpal height (CH) / capitate height (CapH). Results: Although the RI and SL values of angular parameters were similar between the gender groups, the LFI and VT values were significantly higher in the female group (P=0.014 and P=0.004, respectively). All metric parameters were significantly superior in the male group (P<0.001). CHR and rCHR values were similar for proportional parameters, while LUR -values were significantly higher in the male group (P<0.001). All angular measurement parameters, Cord RC, RadH, RadS, LL, LUL, SLD of metric parameters, and CHR and rCHR values of proportional parameters were similar between age groups (P>0.05). While UV values of metric parameters increased in parallel with age, RUD values decreased significantly (P<0.001). The values of the metric parameters CH 3rd MH, CapH, and proportional parameters LUR values also differed between the groups without being correlated with age (P=0.011, P=0.003, P=0.009, P=0.019, respectively). Conclusion: In our study, we have given the measurement parameters that can be used as a reference for the Turkish population, the relationships between gender and age groups, and the variability. These parameters can be helpful in the diagnosis and treatment of wrist pathologies, the design and development of implants for the treatment of wrist pathologies for our population.